Protective Roles for Potassium SK/KCa2 Channels in Microglia and Neurons - Dolga, Amalia M.; Culmsee, Carsten (Frontiers in Pharmacology, 2012)
New concepts on potassium channel function in neuroinflammation suggest that they regulate mechanisms of microglial activation, including intracellular calcium homeostasis, morphological alterations, pro-inflammatory cytokine release, antigen presentation, and phagocytosis. Although little is known about voltage independent potassium channels in microglia, special attention emerges on small (SK/KCNN1-3/KCa2) and intermediate (IK/KCNN4/KCa3.1)-conductance calcium-activated potassium channels as regulators of microglial activation in the field of research on neuroinflammation and neurodegeneration. In particular, recent findings suggested that SK/KCa2 channels, by regulating calcium homeostasis, may elicit a dual mechanism of action with protective properties in neurons and inhibition of inflammatory responses in microglia. Thus, modulating SK/KCa2 channels and calcium signaling may provide novel therapeutic strategies in neurological disorders, where neuronal cell death and inflammatory responses concomitantly contribute to disease progression. Here, we review the particular role of SK/KCa2 channels for [Ca2+]i regulation in microglia and neurons, and we discuss the potential impact for further experimental approaches addressing novel therapeutic strategies in neurological diseases, where neuronal cell death and neuroinflammatory processes are prominent.